2023
DOI: 10.1021/acs.nanolett.3c01638
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Control of Nonferroelastic Ferroelectric Domains in ErMnO3

Abstract: Mechanical pressure controls the structural, electric, and magnetic order in solid-state systems, allowing tailoring of their physical properties. A well-established example is ferroelastic ferroelectrics, where the coupling between pressure and the primary symmetry-breaking order parameter enables hysteretic switching of the strain state and ferroelectric domain engineering.Here, we study the pressure-driven response in a nonferroelastic ferroelectric, ErMnO 3 , where the classical stress−strain coupling is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that the vortex domains can be unfolded into mono-chiral topological stripes through high-temperature straining, via the opposite motion of vortices and antivortices ( 38 ), which suggests that the strain/strain gradient is an effective means to manipulate the vortex cores. The latest research endeavors extend this concept to pressure-driven domain engineering, substantiating that applied pressure at high temperature can indeed regulate the frequency and orientation of the induced stripe-like domains ( 39 ). However, high-temperature straining is rather inaccessible and highly uncontrollable.…”
Section: Resultsmentioning
confidence: 93%
“…It has been demonstrated that the vortex domains can be unfolded into mono-chiral topological stripes through high-temperature straining, via the opposite motion of vortices and antivortices ( 38 ), which suggests that the strain/strain gradient is an effective means to manipulate the vortex cores. The latest research endeavors extend this concept to pressure-driven domain engineering, substantiating that applied pressure at high temperature can indeed regulate the frequency and orientation of the induced stripe-like domains ( 39 ). However, high-temperature straining is rather inaccessible and highly uncontrollable.…”
Section: Resultsmentioning
confidence: 93%
“…45,46 While mechanical stress of comparable magnitude has been reported to effect the ferroelectric domain structure. 23 We note, that related thermal activation effects remain to be studied, which goes beyond the scope of this work. In addition, the magnetic field may interact with the magnetic moment of the domain walls, 21 further promoting the movement of vortex cores.…”
Section: (C) At Bothmentioning
confidence: 98%
“…Since the domain structure in single crystals of h-ErMnO 3 was found to be independent of the applied magnetic field up to magnetic fields of 4 T at 2.8 K, 40 we suggest that the observed changes are a consequence of the polycrystalline nature of the sample. It is established that vortex cores in h-RMnO 3 interact with strain fields, and a strain-induced movement of the vortex cores was theoretically 41 and experimentally 23,42,43 demonstrated for temperatures around T c . In our case, given the observed coupling and the geometrically driven ferroelectricity, we propose that strain may arise from magnetostriction, facilitated by the clamping of the individual grains.…”
Section: (C) At Bothmentioning
confidence: 99%
See 1 more Smart Citation